El acceso a créditos por parte de familias de comunidades campesinas y nativas en el Perú - Panduro Chafloque, Fiorela del Rocío (2024)
Access to credit could be one of the main challenges for families residing in Andean and Amazonian regions, due to the lack of documentation suppor ting their economic or commercial activities. In this regard, the study of an economic dynamic that could be positively viewed by the financial and ban king system is proposed. This, in turn, would encourage an improvement in the living conditions of the country's rural and indigenous populations if the land titling process, which previously belonged to the communities to which they belonged, is amplified. The analysis of a complex social, cultural, legal, and economic condition allows detailing positive elements that impact the national economy tangibly.